Visibilités sikhe et musulmane au Royaume-Uni : tentative de comparaison - Vincent Latour (Revue Française de Civilisation Britannique)
Over the past decade (interethnic riots in the North and the Midlands, 9/11 et 7/7/2005), the political academic and media debate on multiculturalism as a mode of incorporation has focused almost exclusively (or indeed, obsessively) on the place of Islam and Muslims in British society. David Cameron’s Munich speech (5 February 2011), which has been so abundantly commented upon, illustrated the extent of that focalisation, as well as its permanence since 9/11 or indeed, since the Rushdie Affair. As a matter of fact, the sudden emergence of the ‘Muslim community’ to the fore of the British political and media scene at the end of the 1980s following the publication of Rushdie’s Satanic Verses has tended to overshadow the Sikhs’ remarkably consistent and co-ordinated mobilisation over the past fifty years. Indeed, they preceded Muslims and other minority groups in the formulation of cultural demands.A decade after the beginning of the questioning of the ‘multicultural consensus’, it seems both relevant and timely to look into two distinct visibility strategies, in order to identify both divergences and convergences. This paper will be divided into two parts. First, a historical record of the presence of Sikhs and Muslims in Britain shall be drawn, with a special reference to worship-related aspects, which provided early signs of both communities’ visibility across the Channel. Then, part two shall endeavour to compare the Sikhs’ and Muslims’ modes of community mobilisation and the way each group has managed to formulate cultural demands, including in a context characterised, seemingly, by a profound questioning of multiculturalism.